2020
DOI: 10.1093/femsec/fiaa177
|View full text |Cite
|
Sign up to set email alerts
|

miCROPe 2019 – emerging research priorities towards microbe-assisted crop production

Abstract: The miCROPe 2019 symposium, which took place from 2–5 December 2019 in Vienna, Austria, has unified researchers and industry from around the world to discuss opportunities, challenges and needs of microbe-assisted crop production. There is broad consensus that microorganisms—with their abilities to alleviate biotic and abiotic stresses and to improve plant nutrition—offer countless opportunities to enhance plant productivity and to ameliorate agricultural sustainability. However, microbe-assisted cultivation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The assessed microbial taxa formed complex co-occurrence networks in each infested soil with several central taxa conserved across the three soils. Soil-dependent factors have repeatedly been documented as important drivers of plant-associated microbial composition (Peiffer et al, 2013;Chemidlin Prevost-Boure et al, 2014;Xue et al, 2018;Hohmann et al, 2020). Our data is in line with this fundamental observation but also suggested that several taxa form a core of key players of the PRRC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The assessed microbial taxa formed complex co-occurrence networks in each infested soil with several central taxa conserved across the three soils. Soil-dependent factors have repeatedly been documented as important drivers of plant-associated microbial composition (Peiffer et al, 2013;Chemidlin Prevost-Boure et al, 2014;Xue et al, 2018;Hohmann et al, 2020). Our data is in line with this fundamental observation but also suggested that several taxa form a core of key players of the PRRC.…”
Section: Discussionsupporting
confidence: 88%
“…Together, these findings indicated a relation between host genotype, microbial composition, and disease resistance. In light of such findings, plant breeding offers the opportunity to harness positive plantmicrobe interactions and strengthen crop resistance (Wei and Jousset, 2017;Hohmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of these approaches is that they recruit ISR-inducing bacteria under the prevailing crop cultivation conditions, enhancing the chances that they are indeed functional under these conditions. In addition, several studies have argued for new crop breeding strategies that enhance the ability of crops to better exploit associations with beneficial microbes by enhanced attraction of beneficials, enhanced symbiosis, or enhanced plant responses to this symbiosis (e.g., [121]). Several studies have revealed the plant genetic underpinnings of enhanced microbially induced pest suppression (e.g., [122]), making this a viable prospect that can be tailored specifically to ISR-inducing microbes.…”
Section: Approaches To Enhance the Exploitation Of Isr-inducing Microbes In Sustainable Agriculture And Horticulturementioning
confidence: 99%
“…Simultaneously evaluating diverse sorghum genotypes for genetic chilling tolerance and microbe-enhanced chilling tolerance would leverage a novel synergistic approach to early season chilling tolerance. Plant genotype-environment-microbe interactions in field conditions are highly complex (Bakker et al 2020, Hohmann et al 2020, Oyserman et al 2019)). Developing broadly effective microbial enhancements for plant abiotic stress will require incorporating plant genotype – microbe – environment interactions in controlled experiments.…”
Section: Introductionmentioning
confidence: 99%